Affordable bathroom upgrades : transform your bathroom on a small budget - Cory, Steve (Creative Homeowner, 2012)
"Provides alternatives to a costly full-scale renovation by offering inexpensive design ideas and easy step-by-step projects that can help you achieve the bathroom of your dreams, even on a limited budget. You can then decide to make a number of the improvements all at once or space them out to accommodate your time and checkbook" -- P. [4] of cover.